Coupled effect of ageing and temperature in the mechanical behaviour of a polyamide. (August 2016) - Reis, J.M.L.; de Sant́anna, T.; Coutinho, P.P.; Monteiro, A.H.; Teixeira, S.C.S.; Chaves, E.G.; da Costa Mattos, H.S.
Abstract: The present work is concerned with the thermo-mechanical analysis of a particular aliphatic polyamide with long alkyl chains used in the internal sheath of flexible pipes. The main focus is to analyse the coupled influence of temperature and ageing on its mechanical behaviour and fracture. Fracture and tensile tests were performed over a wide range of temperature (from −5 °C to 90 °C) and of corrected inherent viscosity (between 1.0 dl/g and 1.8 dl/g). For higher values of the CIV, the material presents superplastic behaviour, but the behaviour tends to be brittle for lower values of the inherent viscosity and temperature. A general model is proposed for the uniaxial behaviour (valid for a wide range of temperature and inherent viscosity) and also for the fracture behaviour. Experiments are compared with the model predictions and show good agreement.